Dynamic contrast enhanced MRI of bone marrow oedema in rheumatoid arthritis. Issue 2 (26th October 2007) - Hodgson, R; Grainger, A; O'Connor, P; Barnes, T; Connolly, S; Moots, R
Abstract : Aims: The aim of this work was to assess the feasibility of using dynamic contrast enhanced (DCE) MRI of bone marrow oedema, to compare it with conventional marrow oedema scoring systems, and to determine the effects of anti-tumour necrosis factor (TNF)α therapy. Methods: The wrist and metacarpophalangeal (MCP) joints of 25 patients with rheumatoid arthritis were studied. A total of 14 were imaged before and 1–2 weeks after anti-TNFα therapy. T2-weighted fat-suppressed images were collected. A dynamic series of 24 3D spoiled gradient-echo images were acquired before, during and after the intravenous administration of gadolinium-based contrast medium. Oedema was scored using the conventional Rheumatoid Arthritis MRI Scoring (RAMRIS) system from T2-weighted images. The relative enhancement rate (RER) was calculated using the dynamic series from oedematous bone, bone adjacent to oedema and from an uninvolved bone. Results: A total of 56% of patients showed bone marrow oedema. The RER was significantly increased in and adjacent to areas of marrow oedema. There was a significant reduction in the RER after treatment, but not in the RAMRIS score. Conclusions: Dynamic contrast enhanced MRI of bone marrow oedema yields additional information to RAMRIS scoring and may be a more sensitive marker of inflammatory activity and response to treatment.